2012
DOI: 10.1016/j.wear.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A DLC/diamond bilayer approach for reducing the initial friction towards a high bearing capacity

Abstract: Sliding contact mechanics is used to account for the net increase of the bearing capacity of high wearresistant CVD diamond coatings when an outer layer of a DLC lubricant film is deposited on their top surface. Experimental results, namely the critical failure load, taken from reciprocating ball-on-plate tribological testing of such DLC/diamond bilayers, are on the basis of this statement. DC magnetron sputtering was used to grow thin DLC lubricant coatings (non-hydrogenated and hydrogenated varieties) on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The CVD diamond films are composed by grains with dimensions called micro-crystalline diamond (MCD) and nano-crystalline diamond (NCD) varieties, usually classified by their grain size of larger or smaller than 500 nm, 1 which results in the distinct tribological properties of MCD and NCD films. 2,3 However, the chemical-reactive wear including diffusion, oxidation, graphitization, and carbide formation between carbon steel and diamond strongly restrict the wide application of diamond films 4,5 as the carbon steel is almost the most important basic industrial material.…”
Section: Introductionmentioning
confidence: 99%
“…The CVD diamond films are composed by grains with dimensions called micro-crystalline diamond (MCD) and nano-crystalline diamond (NCD) varieties, usually classified by their grain size of larger or smaller than 500 nm, 1 which results in the distinct tribological properties of MCD and NCD films. 2,3 However, the chemical-reactive wear including diffusion, oxidation, graphitization, and carbide formation between carbon steel and diamond strongly restrict the wide application of diamond films 4,5 as the carbon steel is almost the most important basic industrial material.…”
Section: Introductionmentioning
confidence: 99%
“…10 Therefore, researchers recently proposed to fabricate bi-layered diamond/DLC composite films by depositing a top-layer DLC coating on CVD diamond film with expectation of obtaining a novel diamond/DLC composite film that is expected to be able to combine the advantages of two individual films and compensates disadvantages for each other. [11][12][13][14][15] It can be arrived from the above studies that combining CVD diamond and DLC coatings might be a potential method to develop novel tribological coating materials with superior tribological properties. Therefore, the combining application of the diamond/DLCcoated drawing dies and water-lubricating technique may provide an effective approach to improve the efficiency of metal drawing production.…”
Section: Introductionmentioning
confidence: 99%
“…18 Amaral et al also reported the reduction on the friction coefficient of MCD coating by depositing a top layer of DLC coating; moreover, they also found depositing an outlayer of the DLC coating could also increase the bearing capacity of the single-layered diamond coating. 19 Hanyu et al reported the improved antisticking property to aluminum alloy of CVD diamond coated cutting tools with a top-layered DLC coating. 20 Csorbai et al obtained a pinhole free thin diamond-DLC bilayered coating by depositing a layer of the DLC coating on the CVD diamond film and used it as the corrosion protection coating.…”
Section: Introductionmentioning
confidence: 99%
“…also reported the reduction on the friction coefficient of MCD coating by depositing a top layer of DLC coating; moreover, they also found depositing an outlayer of the DLC coating could also increase the bearing capacity of the single-layered diamond coating. 19 Hanyu et al. reported the improved antisticking property to aluminum alloy of CVD diamond coated cutting tools with a top-layered DLC coating.…”
Section: Introductionmentioning
confidence: 99%